Determination of the effect of product substitutability on sales performance of integrated and decentralised supply chains through Nash equilibria. Issue 7 (19th August 2014) - Wang, Renwen; Zhao, Shuliang; Song, Wei; Cacciolatti, Luca; Zhang, Xinyue; Sausman, Chris; Fu, Yelin; Heap, John
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose The paper aims to investigate the effects of product substitutability on sales performance of integrated and decentralised supply chains. We model supply chain performance effects by applying a Cournot equation to a combination of different industry configurations. The study aims to extend existing equilibria models in different supply chains by including the effects of product substitutability on supply chain performance. By extending existing equilibria models, we explore the relationship between the degree of product substitutability, chain structure and chain performance when some actors of the supply chain behave as Stackelberg leaders in a duopoly. Design/methodology/approach The paper models a supply chain performance by applying a Cournot equation to different supply chain structures in a duopoly. Findings Our findings indicate that, for each specific supply chain structures in different market configurations, when product substitutability reaches a certain threshold decentralised supply chains outperform integrated chains, in disagreement with common belief in current existing literature. Research limitations/implications The study is limited to the application of differential equations in a competitive market configured as a duopoly. Future studies might extend the same model to a competitive market characterised by more than two actors. The findings imply that current tendency of lean implementations through integrated supply chains does not always favour supply chain performance. Practical implications The paper includes implications for the development a stronger differentiation strategy based on consumer value when markets are characterised by high product substitutability. Originality/value These findings highlight the importance of differentiation and consumer-value generation in markets that follow Nash equilibria as opposed to the current focus on price competition.